2014
DOI: 10.1586/17474124.2014.943187
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-1 antitrypsin and liver disease: mechanisms of injury and novel interventions

Abstract: α-1-Antitrypsin (α1AT) is a serum glycoprotein synthesized in the liver. The majority of patients with α1AT deficiency liver disease are homozygous for the Z mutant of α1AT (called ZZ or 'PIZZ'). This mutant gene directs the synthesis of an abnormal protein which folds improperly during biogenesis. Most of these mutant Z protein molecules undergo proteolysis; however, some of the mutant protein accumulates in hepatocytes. Hepatocytes with the largest mutant protein burdens undergo apoptosis, causing compensato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 54 publications
1
36
0
3
Order By: Relevance
“…Here, we chose to target Exon V of the human SERPINA1 gene encoding for α1-antitrypsin (AAT). A well described G > A point mutation on base number 31 of this Exon leads to a missense amino acid replacement (E342K) resulting in expression of Z-AAT, which is the underlying cause for clinical severe AAT deficiency18. In order to test whether it was possible to use the G > A point mutation for allele-specific targeting of the Z-AAT allele, we cloned either the 59 bp target sequence of Z-AAT or the target sequence of the normal SERPINA1 allele (M-AAT) into the reporter vector.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we chose to target Exon V of the human SERPINA1 gene encoding for α1-antitrypsin (AAT). A well described G > A point mutation on base number 31 of this Exon leads to a missense amino acid replacement (E342K) resulting in expression of Z-AAT, which is the underlying cause for clinical severe AAT deficiency18. In order to test whether it was possible to use the G > A point mutation for allele-specific targeting of the Z-AAT allele, we cloned either the 59 bp target sequence of Z-AAT or the target sequence of the normal SERPINA1 allele (M-AAT) into the reporter vector.…”
Section: Resultsmentioning
confidence: 99%
“…Several mutations at the SERPINA1 locus have been described to be the causative for AAT deficiency and particularly the E342K point mutation at the beginning of Exon V is related with a severe clinical course. Patients often present a progressive lung disease, such as chronic obstructive pulmonary disease (COPD) and a fraction of them present variable degrees of chronic liver damage, ranging from mild fibrosis to cirrhosis or even hepatocellular carcinoma18. E342K-AAT is prone to self-agglutination and cannot be properly secreted from hepatocytes in the liver, where accumulation inside the endoplasmic reticulum can cause liver disease, whereas lung disease is a consequence of severely reduced AAT serum-concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Результаты недавних исследований показывают, что каскад повреждения клеток запускается в небольшой популяции гепатоцитов, имеющих наибольшее накопление мутантного полимеризованного альфа-1-антитрипсина. Указанные гепатоциты, а их только несколько процентов от общего числа клеток, возможно, имеют повышенную активацию каспазы и повышенную восприимчивость к апоптозу [29,41].…”
Section: обзоры литературыunclassified
“…4,36 Given the high degree of variability among patients with this same ZZ genotype, it is thought that there is likely to be a large influence of genetic and environmental modifiers on the final development of end-organ injury. 1,25 The recognition of these key steps in the pathophysiology, especially the identification of autophagy as a key pathway, and the first publication of an overall, unified scheme of the injury cascade has driven a new era in therapeutic development aimed at AAT liver disease. 23,25 Studies in the mouse model of AAT deficiency have identified more than 10 compounds that effectively block liver injury, although none are yet approved for human use (►Fig.…”
Section: Pathophysiology Of Aat Disease New Insights and Human Trialsmentioning
confidence: 99%
“…The risk of life-threatening liver disease in children is 3 to 5%, although many children may have self-limited neonatal cholestasis or mild serum aminotransferase elevations. 1,7 In the neonatal period, 20% of ZZ patients present with the "neonatal hepatitis syndrome," which includes cholestatic jaundice, pruritus, poor feeding, poor weight gain, hepatomegaly, and splenomegaly. 7,8 Liver biopsy findings may be highly variable in infants including giant cell transformation, lobular hepatitis, significant steatosis, fibrosis, hepatocellular necrosis, bile duct paucity, or bile duct proliferation.…”
mentioning
confidence: 99%